2009
DOI: 10.1093/annonc/mdp025
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular toxicity following sunitinib therapy in metastatic renal cell carcinoma: a multicenter analysis

Abstract: Patients undergoing sunitinib, especially those with a previous history of hypertension and coronary heart disease, are at increased risk for cardiovascular events and should be monitored for exacerbations of their hypertension and for evidence of LVEF dysfunction during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(126 citation statements)
references
References 21 publications
2
117
1
6
Order By: Relevance
“…18 Sunitinib has been associated with many side effects, including severe cutaneous toxicities and cardiotoxicity. 11,[19][20][21][22] To avoid these side effects, targeted delivery of sunitinib to the target cells, ie, the proximal tubular cells of the kidneys, is a comprehensive approach. We have shown that small-molecule inhibitors can be delivered to the kidney by conjugation to lysozyme, [23][24][25] a low molecular weight protein that is rapidly filtered through the glomeruli of the kidneys and subsequently taken up at the apical membrane of proximal tubular cells via megalin receptor-mediated internalization.…”
Section: Introductionmentioning
confidence: 99%
“…18 Sunitinib has been associated with many side effects, including severe cutaneous toxicities and cardiotoxicity. 11,[19][20][21][22] To avoid these side effects, targeted delivery of sunitinib to the target cells, ie, the proximal tubular cells of the kidneys, is a comprehensive approach. We have shown that small-molecule inhibitors can be delivered to the kidney by conjugation to lysozyme, [23][24][25] a low molecular weight protein that is rapidly filtered through the glomeruli of the kidneys and subsequently taken up at the apical membrane of proximal tubular cells via megalin receptor-mediated internalization.…”
Section: Introductionmentioning
confidence: 99%
“…This is a significant issue because such symptoms might be due to sunitinib-induced hypothyroidism and could therefore be reversible with thyroid hormone replacement. Secondly, fatigue can also be related to cardiac failure, which also has recently been reported as an important side effect of sunitinib (Chu et al, 2007;Schmidinger et al, 2008;Telli et al, 2008;DiLorenzo et al, 2009). Unfortunately, detailed information on cardiac toxicity is also lacking, but the authors reported that at least one patient died because of treatment-related congestive heart failure.…”
Section: Sirmentioning
confidence: 99%
“…In addition, unrecognized hypothyroidism or thyrotoxicosis may affect the metabolism of other medications [151]. Finally, it should be considered that thyroid dysfunction, although rarely, can lead to life-threatening consequences in cancer patients, as warned by case reports of patients who experienced myxedematous coma [152] or impaired cardiac function [153,154] as a complication of TKIinduced hypothyroidism (i.e. sunitinib).…”
Section: Why Is It Important To Assess Thyroid Function In Cancer Patmentioning
confidence: 99%